An Analysis of Teachers Use of Hands-On Instructional Media on Students’ Engagement in The English for Young Learners’ Classes (A Case Study at SDN 1 Terong Tawah) - Aditia, Yusril; Waluyo, Untung; Farmasari, Santi; Soepriyanti, Henny (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2024)
This study investigates the implementation process, focusing on teaching methods, challenges encountered, and outcomes achieved. Employing a qualitative research design, data were gathered through classroom observations, teacher interviews, and analysis of lesson plans and teaching materials. Findings reveal that while teachers employ innovative strategies to engage students, their efforts are constrained by insufficient training and limited institutional support. Student engagement and comprehension vary, influenced by both instructional methods and the learning environment. The findings suggest that enhancing teacher training programs, providing adequate resources, and fostering collaboration among educators and stakeholders can significantly improve the effectiveness of the local content curriculum. Policymakers must prioritize systemic support to address challenges and ensure English instruction contributes effectively to students' language development and academic success.